Voluntary Disclosure Schemes for Offshore Tax Evasion: An Analysis - Matthew Gould; Matthew Rablen (Center for Economic Studies and ifo Institute (CESifo), 2016)
In recent years tax authorities worldwide have implemented voluntary disclosure schemes to recover tax on offshore investments. Such Schemes are characterized by the acquisition of non-audit information on offshore holdings, and a subsequent opportunity for affected taxpayers to make a voluntary disclosure. Accepted disclosures are subject to a discounted .ne rate, but verified under-disclosure attracts a higher penalty. We characterize the optimal Scheme and show that an optimal Scheme can generate a Pareto-improvement over the optimal auditing equilibrium without a Scheme, and can stimulate legitimate offshore investment activity. We show when a tax authority optimally gives incentives for truthful disclosure, and when it does not. The analysis yields practical design insights for policymakers.
Keywords: H26; D85; 330; voluntary disclosure; offshore tax evasion; tax amnesty; third-party information